Análisis de parámetros hidrodinámicos para la generación de energía hidráulica en piscigranjas de Zungarococha, Loreto - Wong Meléndez, Margarita Alessandra (2025)
This research was conducted at Fundo Sarita, located in Zungarococha, Loreto, with the aim of evaluating the energy potential of fish farm water falls through the analysis of hydrodynamic parameters. The study was conceived as a preliminary assessment aimed at exploring small‑scale power generation alternatives that could help reduce the region’s dependence on fossil fuels. Four fish farms with water falls presenting favorable conditions for energy utilization were identified and georeferenced. Subsequently, key parameters such as flow velocity, hydraulic depth, discharge, head height, and channel slope were measured using field methodologies, including float techniques, topographic surveys, and bathymetric calculations. Based on these data, both real and theoretical energy potentials were estimated using the potential energy formula and Manning’s equation, while also considering operational efficiency losses between 50% and 70%, according to the literature. The results showed that the practical energy potential reached 17.34 kW, whereas the theoretical potential was 132.81 kW, placing these water falls within the range of micro and mini hydroelectric plants under Peruvian regulations. It was estimated that this capacity could supply between 93 and 719 households per month, depending on the efficiency considered. This study represents a first step toward future small‑scale hydroelectric projects in Loreto, providing technical information that supports the diversification of the energy matrix and the promotion of sustainable solutions in rural and peri‑urban areas.